The Influence of the Sacred Texts on the Visual Configuration of the Warrior Saints - Olivares Torres, Enric (Eikón / Imago, 2020)
This article analyzes the conventionalities and visual resources used in the legends of holy warriors, based on the sources of the Old and New Testaments in order to offer a better understanding of the phenomenon of the sacralization of war and the function of the images of holy knights in the Hispanic context. There are many examples in which the holy warriors repeatedly appear to protect the Christian armies or to destroy the enemy hosts. In many of these cases, some of the significant elements used present an evident association with the great deeds of the Old Testament, conforming as recurrent in the visual tradition.